Time-heterogeneous impacts of global temperature cycle on world business cycle - Kyungsik Nam (Journal of Applied Economics, 2024)
We study the statistical relationship between the world business cycle and the global temperature cycle. To amplify the signal-to-noise ratio, we estimate a two-state latent dynamic process from the original data using the endogenous regime-switching methodology. Subsequently, we apply a time-varying structural VAR analysis to identify the time-heterogeneous relationship between the extracted latent factors. Our findings provide empirical evidence that the global mean temperature cycle has a negative impact on the world business cycle during super El Ni\~no periods, which are characterized by relatively high temperature variance records given the past information.
Keywords: C13; C51; E32; Q54; 330; Climate change; global temperature anomaly; structural VAR model; world business cycle